The Security Team Organizational Commitment - Afiatin Nuuroini (Universitas Airlangga, 2022)
According to a survey, one of the world's largest financial firms, the ideal time to stay in a job is 3-5 years. Meanwhile, the tenure of PT.Suprama Security Team as of January 1, 2020 is 6-23 years, stating that they have strong organizational commitment. Organizational commitment influences the decision whether or not to stay in organization, which has an impact on performance, employee turnover, absenteeism, organizational climate and employee attitudes in the team. To capture this situation, qualitative research methods were used with in-depth interview techniques conducted on 10 out of 30 informants. The results show that organizational commitment is formed by financial and non-financial factors such as a comfortable work environment, good relationships with colleagues, clarity of status as permanent employees, friendly superiors, and conscientious work operational standards. It shows that the organizational commitment the security team has is dominated by continuous commitment, affective commitment and normative commitment, respectively.